Generalized Wideband Cyclic MUSIC. (29th September 2009) - Liu Liu, Zhang-Meng Zhang-Meng; Huang Huang, Zhi-Tao Zhi-Tao; Zhou Zhou, Yi-Yu Yi-Yu
Abstract : The method of Spectral Correlation-Signal Subspace Fitting (SC-SSF) fails to separate wideband cyclostationary signals with coherent second-order cyclic statistics (SOCS). Averaged Cyclic MUSIC (ACM) method made up for the drawback to some degree via temporally averaging the cyclic cross-correlation of the array output. This paper interprets ACM from another perspective and proposes a new DOA estimation method by generalizing ACM for wideband cyclostationary signals. The proposed method successfully makes up for the aforementioned drawback of SC-SSF and obtains a more satisfying performance than ACM. It is also demonstrated that ACM is a simplified form of the proposed method when only a single spectral frequency is exploited, and the integration of the frequencies within the signal bandwidth helps the new method to outperform ACM.